An animal model of female adolescent cannabinoid exposure elicits a long-lasting deficit in presynaptic long-term plasticity. (December 2015) - Lovelace, Jonathan W.; Corches, Alex; Vieira, Philip A.; Hiroto, Alex S.; Mackie, Ken; Korzus, Edward
Abstract: Cannabis continues to be the most accessible and popular illicit recreational drug. Whereas current data link adolescence cannabinoid exposure to increased risk for dependence on other drugs, depression, anxiety disorders and psychosis, the mechanism(s) underlying these adverse effects remains controversial. Here we show in a mouse model of female adolescent cannabinoid exposure deficient endocannabinoid (eCB)-mediated signaling and presynaptic forms of long-term depression at adult central glutamatergic synapses in the prefrontal cortex. Increasing endocannabinoid levels by blockade of monoacylglycerol lipase, the primary enzyme responsible for degrading the endocannabinoid 2-arachidonoylglycerol (2-AG), with the specific inhibitor JZL 184 ameliorates eCB-LTD deficits. The observed deficit in cortical presynaptic signaling may represent a neural maladaptation underlying network instability and abnormal cognitive functioning. Our study suggests that adolescent cannabinoid exposure may permanently impair brain functions, including the brain's intrinsic ability to appropriately adapt to external influences. Highlights: We used female mice to model adolescent cannabinoid exposure. We examine changes presynaptic long-term potentiation (LTP). Endocannabinoid-LTP and mGluR2/3-LTP are impaired in model for adolescent cannabinoid exposure. Adolescent CB1R agonist exposure triggers cognitive deficiency.